Silver and lead telluride based thermoelectric nanostructured materials - Zhou, Wenwen (2013)
Lead telluride (PbTe) and its multi-phased alloy are well accepted as promising materials for high figure of merit (ZT) thermoelectric devices because of their high Seebeck coefficient, S, low thermal conductivity, k, and high electric conductivity,, in the temperature range 400-700 K. For further enhancement of the thermoelectric performance, reducing the dimension of the thermoelectric semiconductor has been reported as a successful strategy to further improve their thermoelectric property (ZT value) because of the quantum size effect and the enhancement of phcnons interface scattering.